"Digital workflow for a complete-arch fixed implant-supported prosthesis: a clinical case.". (June 2022) - Bañuelos, Ricardo Palacios; Anglada, Albert; Cantó, Oriol; Quintana, Pau
Abstract : Purpose: The digital flow and the planning of fully guided protocols in implantology allow to obtain more predictable results with greater precision reducing treatment time, as well as obtaining greater patient comfort during treatment. Methods: A 58-year-old female patient with upper and lower teeth with poor periodontal prognosis, class III mobility and dental malposition as a result of periodontal disease was admitted. The treatment plan was to perform extractions of the remaining teeth and placement of immediate implants with a fully guided protocol to ensure the ideal position of the implants and the future restoration in the upper arch, in addition to performing immediate loading with a full-arch milled PMMA (Polymethyl Methacrylate) prosthesis screwed to multiunits. Surgery was performed and an intraoral scan was taken with scanbodies on multiunit with Prime Scan. In addition, a CT was taken with the scanbodies and a provisional is drilled for immediate loading. Results: With this protocol we were able to achieve fully guided implant placement immediately after extractions, taking an intraoral scan and fabricating a milled PMMA provisional screwed to the multiunits. We could provide an immediate prosthesis that had the aesthetic and functional parameters, offering the patient a provisional and comfortable solution during the implant integration phase. Conclusions: The digital flow in guided surgery allows the placement of implants in the planned position with the loading of a transitional prosthesis that complies with functional and esthetic requirements.